Development of halal slaughterhouse as an effort to strengthen the halal supply chain through a collaborative governance approach - Susilo Wati; Sylfia Rizzana; Zaid Barzenji (Yayasan Azhar Amanaa Yogyakarta, 2025)
Indonesia has significant potential in the halal meat market, yet faces major challenges in ensuring product availability and halal assurance across the supply chain. One of the key obstacles is the limited number of certified halal slaughterhouses. This study aims to develop an integrated halal slaughterhouse model through multi-stakeholder collaboration, applying a Collaborative Governance approach within the halal supply chain context in Indonesia. The involvement of key actors—government, industry, certification bodies, communities, and academics—is essential to create a more transparent, accountable, and traceable halal ecosystem. Through the implementation of collaborative governance, Indonesia can reduce the halal meat deficit, improve the competitiveness of halal products in international markets, and accelerate digital transformation in halal supply chains. Furthermore, this study addresses a critical research gap regarding traceability integration in halal slaughterhouses and provides practical policy recommendations. East Java is selected as the research location due to its strategic role as a livestock production center and its large Muslim population, making it a region with high potential for halal market development.